After Nature: The Expanded Landscapes of Ana Mendieta and Ana Vaz (Cinéma & Cie. Film and Media Studies Journal, 2020)
The article explores women’s interventions into landscape through the experimental practices of Cuban American multimedia artist Ana Mendieta and contemporary Brazilian visual artist and filmmaker Ana Vaz. Interested in the material and metaphorical intersections among film, landscape, and geology, I focus on the geological imagination of landscape partaking in Mendieta’s and Vaz’s art while asking what sorts of aesthetic regimes and formal strategies they choose to express it. Mendieta’s comprehension of earth as matter, medium, and a deep surface for inscription of traces comments on the materiality of film as a recording medium from the point of view of geologically oriented art. Vaz’s landscape, inflected with human interventions, emerges as an enormous living medium of memory, linking its exploration to a geological approach and the work of excavation while transforming deep time into what the artist calls ‘cinematographic multiperspectivism’. The article argues that it is the attention to the geological that unites these two artists in their critique of the position of exteriority and of landscape as an object of contemplation. Mendieta and Vaz depart from traditional aesthetics of landscape as a view by moving toward landscape as a network of relations among humans, memories, and times.